Can an FDA-Approved Alzheimer’s Drug Be Repurposed for Alleviating Neuronal Symptoms of Zika Virus? - Devika Sirohi (American Society for Microbiology, 2017)
ABSTRACT Zika virus caught the world by surprise by its rapid spread and frightening disease outcomes. This major epidemic motivated many scientists to focus their attention on controlling this emerging pathogen. As many as 45 vaccine candidates are being developed, but progress in the antiviral arena has been slower. In a recent article (mBio 8:e00350-17, 2017, https://doi.org/10.1128/mBio.00350-17 ), Costa and colleagues showed that an FDA-approved drug used to treat Alzheimer’s disease may moderate Zika virus-induced neuronal damage. This work is based on the premise that overstimulation of N-methyl-d-aspartate receptors (NMDARs) may drive neurodegeneration and that this may be responsible for neuronal cell death associated with Zika virus infection of the central nervous system (CNS). Thus, blockage of the NMDAR channel activity with FDA-approved memantine or other antagonists may reduce neurological complications associated with Zika virus infection. Repurposing a preapproved drug and targeting the host represent intriguing strategies and yet require more analysis prior to moving into clinical trials.